2012
DOI: 10.1097/tp.0b013e31826f135e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Donor Kidney Volume on Recipient Outcome

Abstract: Donor kidney volume dosing is an important determinant of recipient graft outcomes and may predict recipient kidney function in kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…However, after kidney volume was corrected for body surface area there was no sex difference, analogous to what it is known about GFR where there is no or minimal difference in corrected GFR between sexes. Similar findings were later reported by another single-center study [37].…”
Section: Donor Kidney Size and Its Implications To Donor And Recipiensupporting
confidence: 81%
See 1 more Smart Citation
“…However, after kidney volume was corrected for body surface area there was no sex difference, analogous to what it is known about GFR where there is no or minimal difference in corrected GFR between sexes. Similar findings were later reported by another single-center study [37].…”
Section: Donor Kidney Size and Its Implications To Donor And Recipiensupporting
confidence: 81%
“…This also holds true in living donation, where it has been noted that the donor kidney-recipient body size mismatch ("nephron under dosing") can lead to poor allograft function [44]. Transplantation of donor-recipient pairs with a transplant kidney volume-recipient body weight ratio less than 2 cm 3 /kg was associated with significantly worse graft function [37]. Poggio et al [31] showed that a transplanted kidney volume greater than 120 cc/1.73 m 2 was independently associated with better estimated GFR at 2 years post-transplant when compared with recipients of lower transplanted kidney volumes (64+/−19 mL/min/1.73 m 2 vs 48+/−14 mL/min/ 1.73 m 2 , p<0.001).…”
Section: Donor Kidney Size and Its Implications To Donor And Recipienmentioning
confidence: 94%
“…We confirmed in our cohort as well as in an external validation cohort that the variable rk-GFR/vol was inversely associated with 5-year functional gain after controlling for age. It has already been reported that larger kidney volume estimated by CT scan was associated with better graft function (13)(14)(15). It has also been shown that the initial preserved kidney volume adjusted for body surface area is correlated with donor renal function at 6 months (31) and 1 year postdonation (17).…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, the combination of predonation GFR measurement and nuclear SRF enables us to calculate the initial GFR of the remaining kidney (rk-GFR). Furthermore, it has been suggested that measurements of the volumes of the kidney to be donated and the remaining kidney using renal computed tomography scan (CT scan) are predictive of subsequent renal functions in the recipient (13)(14)(15) and the donor (16,17), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Renal length and volumes also correlate with recipient renal function up to 36 months after transplantation. A low ratio of cortical volume to recipient weight has been associated with diminished graft function at 36 months (45)(46)(47). Hence, volumetric measurements are now becoming an important tool in selecting laterality, along with nephron dose matching with the recipient (Figure 7).…”
Section: Computed Tomographymentioning
confidence: 99%